Schaums outline of theory and problems of introduction to digital systems - James Palmer; Perlman, David E (Chennai McGraw Hill Education India Pvt Ltd, 2020)
This invaluable book teaches readers a unified design methodology. After providing some introductory material, it guides students through msi and LSI combinatorial Loci elements, emphasizing devices that can be programmed for specific applications. The rest of the book deals mainly with synchronous sequential logic. Throughout, problems with step-by-step solutions and delayed answers help readers gauge their progress, deepen their comprehension, and sharpen their analytical skills.
Keywords: Binary System; Combination Logic; MSI LSI Elements; Timing Diagrams